Keefektifan Penyampaian Pesan Islam Melalui Trend (Pesantrend) Di Era Digital - Muhamad Parhan; Maimunah Zilallah; Gabriela Oktaviani Subrata; Asma Khari; Sheila Mitha Nurahmi Subadri (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This article aims to explain the effectiveness of da'wah in the form of delivering messages through trends (PesanTrend) in the digital era with the use of social media, especially Instagram, Facebook, and Youtube and to compare the effectiveness of conventional da'wah with Pesantrend da'wah. By utilizing internet facilities, millennial preachers can create Islamic content that is packaged in slang and related to stories of daily life and can be added with funny things so that it can attract and invite the younger generation to watch and apply it for good. This research is a descriptive research with a qualitative approach. The sample of this study were Indonesian citizens of generation Z aged 18-22 years. The data collection technique used was in the form of an online questionnaire containing questions about the message of da'wah contained in the social media content of Instagram, Facebook, and Youtube. The data obtained were then analyzed descriptively by means of data reduction, data presentation, and drawing conclusions. Based on the results of the study, it can be seen that Instagram tends to be preferred by Generation Z than Youtube and Facebook. This is because Generation Z tends to prefer Islamic content in the form of images rather than videos or writings because image media is considered more attractive and easy to understand. In addition, the current generation of Z also tends to prefer the message of Trending Da'wah to conventional da'wah such as lectures, studies, Islamic learning, and so on